PERILAKU PETANI DALAM PELAKSANAAN PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) DI KABUPATEN PELALAWAN - Rahmi Puspita Sari; Rosnita Rosnita; Roza Yulida (DINAMIKA PERTANIAN, 2016)
The aims of this research to determine the implementation of KRPL Program and farmers habit in KRPL program. The research was conducted in 11 villages of Pelalawan Regency in 2013 with 174 people as samples. The method used is descriptive analysis. The research showed implemention of KRPL program in Pelalawan regency accepted Rp 47.000.000. The coast was spent for environment industry like the source of food or cattle and fish. Developing KRPL program is used by doing 9 steps based on technical guidline of KRPL. The steps are preparation, making grup, socialization, group institution strength, planning activities, coaching implementation, budgeting, monitoring and evaluating. The characteristic of innovation, communication channels, agent of change, characteristic farmers and farmers habit which categorized good with score 3,75, 3,41, 3,53, 3,72, but community leaders which categorized enough (score 3,34). Overall the implementation of KRPL program is welldone because it was supported by program innovation is suitable with farmers needed, there was agent of change help the socialization and communication which is suitable with the role of society and farmers.